Research on New Framework Based on Existing Smart Expressway Construction Guides - Zhuocheng Yang; Liang Hao; Yuchen Liu; Longmei Duan; Chunfu Jia (Journal of Highway and Transportation Research and Development)
This article aims to introduce an innovative framework and associated construction content for the modern smart highway, and to succinctly provide viable recommendations for its rapid development. This study examines the construction frameworks and guidelines across 13 provinces and cities, identifying their commonalities and variations. The new framework is categorized into five layers: Perception, Support, Data, Computing, and Application. The construction key points in these layers are concisely explained and the Application layer is further segmented into six facets: Safety, Efficiency, Green, Convenience, and Toll Collection. This study analyzes the critical application scenarios in various provinces and cities. It aids in rectifying the disparity in understanding during actual construction across these provinces, providing a classification criteria for smart highway construction content. These guidelines will significantly influence future project construction improvements.